Perspektif Ekonomi Islam Terhadap Dampak Pelaksanaan Gadai Sawah Bagi Kesejahteraan Petani di Desa Padang Siring Kecamatan Seginim Kabupaten Bengkulu Selatan - Sari, Mella Nopita Sari; B, Idwal; Hasanah, Uswatun (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of the research is to determine the implementation of pawning rice fields and to determine the impact of implementing pawning rice fields on the welfare of farmers from research method used is qualitative. The data collection techniques used were observation, interviews and documentation. Research results: 1) Implementation of pawning rice fields, namely: First, the pillars and conditions of pawning where in the implementation they have been fulfilled, but in implementing the contract the community does not bring witnesses and only produces written evidence based on trust between both parties. Second, the Rights and Obligations of the Pledge Giver and Pledge Recipient, where in practice the rights of the pledge recipient have been fulfilled but the obligations of the pledge recipient have not been because the pledge recipient is still using the pawned goods for his own benefit. Meanwhile, the rights and obligations of the pledgor have been fulfilled. Third, the use of pawned goods, in practice the pawned goods are used by the pawn recipient. 2) The impact of pawning on farmer’s welfare from an Islamic economic perspective, namely: Dharuriyat, Hajiyat and Tahsiniyat. Where the implementation of this pawn is still far from prosperous, especially for the farmer (pawn giver), because by using the pawned goods by the pawn recipient, the pawn recipient can get multiple profits while the pawn giver lacks a lot of income which makes it difficult to meet his living needs, and it becomes increasingly difficult to pay off debts.